Factors Affecting Farmers’ Willingness to Pay for Agricultural Insurance: A Literature Survey (2004-2023) - Kousar, Rehana; Ahmad, Tusawar Iftikhar; Abbas, Samar; Bhatti, Muhammad Azhar (iRASD Journal of Economics, 2023)
Agriculture is a critical component of many economies, and the livelihood of farmers is often highly dependent on their ability to manage crop and livestock production risks. This study provides a comprehensive synthesis of the existing literature, shedding light on the intricate dynamics shaping farmers' decisions to invest in agricultural insurance. Based on the literature survey made for 54 relevant research studies (conducted between 2004 and 2023), this study presents an extensive review of research on factors affecting farmers' willingness to pay for livestock insurance. The study aggregates and analyzes findings from many sources, offering valuable insights for policymakers, insurance providers, and researchers. The study's findings inform the design of targeted interventions and awareness campaigns to enhance the financial protection of farmers, ensuring their stability in the face of economic and climatic uncertainties. In this way, the findings are significant in the context of global agricultural resilience and food security.